Pengembangan Buku Saku Digital Self-Harm sebagai Media dalam Bimbingan dan Konseling untuk Siswa SMP - Najla Karima; Tri Umari; Kiki Mariah (Universitas Palangka Raya, 2026)
Students’ difficulties in understanding self-harm as a maladaptive behavior and the unavailability of systematic, engaging, and user-friendly informational media for school counselors formed the background of this study. This study aimed to develop a digital pocket book on self-harm as a structured and practical supporting medium for guidance and counseling services. This research employed a Research and Development (R&D) method using the ADDIE model, but the development process was limited to the implementation stage. The research subjects consisted of material experts, media experts, and 10 students as practicality assessors. Data were collected using validation sheets and practicality questionnaires and were analyzed descriptively using qualitative and quantitative approaches. The results showed that the digital pocket book was categorized as highly valid based on media expert assessment, with a percentage of 98.7%, and valid based on material expert assessment, with a percentage of 80.5%. In addition, the practicality test conducted by students showed that the product was highly practical, with a percentage of 92.8%. Therefore, the digital pocket book on self-harm is considered feasible and practical as a supporting medium in guidance and counseling services. This medium can assist school counselors in providing psychoeducational services and help students understand self-harm and its prevention more appropriately.